2020
DOI: 10.1101/2020.04.20.049601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anthrax Toxin Translocation Complex Reveals insight into the Lethal Factor Unfolding and Refolding Mechanism

Abstract: 1Translocation is essential to the anthrax toxin mechanism. Protective antigen, the 2 translocon component of this AB toxin, forms an oligomeric pore with three key clamp sites that 3 aid in the efficient entry of lethal factor or edema factor, the enzymatic components of the toxin, 4 into the cell. LF and EF translocate through the protective antigen pore with the pH gradient 5 between the endosome and the cytosol acting as the driving force. Structural details of the 6 translocation process have remained elu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The ϕ-clamp can stochastically switch between varieties of different diameter conformations, each having a different effect on the liquid–vapor probability transition . The dynamic hydrophobic seal model of protein translocation was also suggested in the recent cryo-EM study that captured a snapshot of the PA 63 channel translocating LF N . The authors report detecting motion of the ϕ-clamp residues (concerted or individual), which may move up and down to accommodate different side chains.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The ϕ-clamp can stochastically switch between varieties of different diameter conformations, each having a different effect on the liquid–vapor probability transition . The dynamic hydrophobic seal model of protein translocation was also suggested in the recent cryo-EM study that captured a snapshot of the PA 63 channel translocating LF N . The authors report detecting motion of the ϕ-clamp residues (concerted or individual), which may move up and down to accommodate different side chains.…”
Section: Resultsmentioning
confidence: 95%
“…32 The dynamic hydrophobic seal model of protein translocation was also suggested in the recent cryo-EM study that captured a snapshot of the PA 63 channel translocating LF N . 67 The authors report detecting motion of the ϕ-clamp residues (concerted or individual), which may move up and down to accommodate different side chains. In addition, the idea about the dynamic behavior of the ϕ-clamp was directly supported in a study when F427 was sitespecifically labeled with p-fluorophenylalanine and investigated using 19 F NMR.…”
Section: ■ Introductionmentioning
confidence: 99%
“…With improvements in modern instrumentation and new algorithms, we envisage an AFM 'resolution revolution' to be on the horizon. examples of nanodiscs [15,[161][162][163], liposomes [39,163], detergent [4] and amphipols [88,164] which have all been used to study the pore and prepore forms of PFPs. Select cryoEM examples; MPEG1 [39], XaxAB [4], Anthrax toxin [15] and polyC9 [88] (C) Microfluidic and in situ time-resolved cryoEM techniques provide structural insight over small increments of time.…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…Broadly, PFPs accomplish biological roles in cell signalling [5][6][7], programmed cell death [8][9][10], killing of other cells and organisms [11,12], defence, development [13,14], delivery of effector molecules [15][16][17][18], as well as providing a means of digestion. The most obvious function of PFPscell killingis achieved by disrupting the membrane bilayer, resulting in either osmotic shock or diffusion of other effector molecules between membrane compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been shown that monoclonal antibodies produced against LF have the most interaction with lethal factor domain1 (LFD1), which indicates the importance of this region (15). LFD1 epitopes are also almost twice as involved in antibody production as any other region (17). To address the shortcomings of the existing vaccines including the improved effectiveness, a fusion construct of two essential domains LFD1 and PA4 was made.…”
Section: Introductionmentioning
confidence: 99%